Analysis Problems of Quranic Education Teachers in Indonesia: A Systematic Literature Review - Engkizar, Engkizar; Jaafar, Azhar; Hamzah, Mohd Isa; Langputeh, Sukree; Rahman, Ikhwan; Febriani, Afifah (Islamic Studies and Development Center in collaboration with Department of Islamic Education Universitas Negeri Padang, 2025)
Quran teachers play a role in producing a generation of Muslims who are able to read, understand, and memorize the Quran. However, reality shows that there are still many problems faced by Quran teachers in Indonesia. This article aims to identify and analyze the problems faced by Quran teachers in Indonesia. This article uses the Systematic Literature Review method with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) approach. A search was conducted on 25 relevant articles from the Scopus and Google Scholar databases published between 2019 and 2024. These articles were analyzed to identify the main issues and solutions that can be applied to improve the quality of Quran teachers. The analysis results indicate that Quran teachers face various challenges, including i) lack of competence in tajweed, ii) low capacity in tahfidz, iii) monotonous teaching methods, iv) absence of standardized guidelines or learning modules, v) lack of formal training, and vi) insufficient training. All these analysis results highlight the need for interventions in the form of developing comprehensive training modules for Quran teachers, as well as recommendations for regular training programs and competency certification for Quran teachers that can be implemented by the government to promote the improvement of national Quran education quality. This analysis is expected to serve as a strategic guide for the government and educational institutions. This analysis is expected to serve as a strategic guide for the government and educational institutions.